Collaborative Governance in Environmental Management for Climate Change Mitigation in Rayeuk Kareung Village, North Aceh - Putri Mandasari; Ferizaldi; Ti Aisyah; Muhammad Hasyem; Maryam (Program Magister Administrasi Publik, 2025)
The issue of environmental governance is a critical urgency as it directly impacts the sustainability of human life. The collaboration among stakeholders requires attention to assess whether it is functioning effectively or not, in order to mitigate environmental governance challenges. This study aims to examine the processes and obstacles encountered in the collaboration between the government and non-governmental organizations in environmental governance in Gampong Rayeuk Kareung and various related stakeholders in Lhokseumawe City. A qualitative descriptive approach is employed, utilizing in-depth interviews, observations, and documentation as data collection methods, followed by data management, data display, and conclusion drawing. The findings indicate that cross-sectoral collaboration has successfully increased environmental awareness among the community, reduced surface water pooling, and met water needs through eco-friendly technologies such as biopore infiltration holes and rainwater harvesting systems. The program's sustainability is supported by the local institution